Percepția calității unor servicii sociale - Novak, Andrei (Calitatea Vieții, 1993)
The way the adult population of Bucharest perceives the quality of some public services and public authorities (institutions) make up a peculiar view of them, that so necessary feed-back. By thinking about either the dysfunctions of the public services or the perception strictly speaking, this study offers the purveyors the opinions of the users.